CGIAR Climate Impact Area Webinar Series - Webinar 3: Carbon Credits: Can they be fixed? - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
Most countries, institutions, companies and individuals will continue to generate greenhouse gas emissions through their activities even as the world decarbonises, meaning many are choosing to compensate for these ‘residual’ emissions. The most common approach for doing so is to purchase carbon credits.